O conceito de confiança em epistemologia do testemunho : distinguindo confiar de fiar-se - Ketzer, Patricia (2015)
Trust is an indispensable concept whenever we think of human beings interacting with other individuals because it helps us to think about the political order and social cooperation. However, it is far from having a single definition. The search for a definition has proved that it is necessary to come back to the origins of the concept in order to seek for understanding its use in Epistemology. In Moral Philosophy, it is established a distinction between two ways of trusting: 1) trust, which is characterized by a deeper interpersonal relationship that involves good will and vulnerability; 2) rely, which is a kind of trust but more basic in how the world and the things work. The concept of trust becomes relevant in Epistemology when we start to consider transmission of knowledge by testimony. The main issue is when we can trust other people to acquire knowledge based on their acts of speech. It is not possible to debate testimony without considering the problem of trust. Nevertheless, the concept has been used inappropriately. The moral aspects do not contribute to the epistemic scenario. However, not considering these aspects mischaracterizes the concept, reducing it to relying only. We defend that, only rely should be, prudently, used. It is a concept that has already been established in Epistemology literature. In order to do so, we analyzed three possibilities: a reduction to the moral field, an analogy between the concept in Moral Philosophy and Epistemology and, at last, a non-analogical use, that is, strictly epistemic. We presented a general sketch of the debate about Epistemology of Testimony and the role of trust in this reduction. We exposed the concept of moral trust and evaluated the possibility of a reduction. Not considering the distinction proposed in Moral Philosophy mischaracterizes the concept. On the other hand, the reduction is not possible because moral trust presupposes risk acceptance, the attempt of eliminating risks through rational thought weakens the act of trusting. Besides, trust makes us resistant to evidences and, in Epistemology, it is wrong to neglect evidences. Interpersonal conceptions propose analogical use of the concept, applying them to epistemological debates without neglecting moral aspects. Nevertheless, they are not a viable option because they are epistemically powerless. The moral bias do not play any relevant epistemic role. Thus, we analyzed the possibility of a non-analogical use, based on Richard Foley’s (2001) proposition. This author does not consider differences between trust and rely. He ends up reducing the concept of trust to the concept of rely, overshadowing the vocabulary in Epistemology of Testimony. We defend that the non-analogical use is a mistake because it mischaracterizes what normally is called trust in order to reduce it to an already fixed concept in epistemological literature. It does nothing but confusions to the debate. Considering moral aspects of trust is important for identifying the problem. The concept of trust cannot contribute to the debate because it does not play an epistemic role. As for the concept of rely, it can be used in Epistemology of Testimony, just as it has been used in other epistemological debates.